Phytochemical constituents and anticancer activities of Tarchonanthus camphoratus essential oils grown in Saudi Arabia - Fahd A. Nasr; Omar M. Noman; Ali S. Alqahtani; Wajhul Qamar; Syed Rizwan Ahamad; Abdullah A. Al-Mishari; Nouf Alyhya; Muhammad Farooq (Elsevier, 2020)
Tarchonanthus Camphoratus L. is traditionally known for its various medicinal purposes. In this study, the T. camphoratus essential oil (TCEO) was isolated via steam distillation, and its chemical constituents were determined using GC-MS. The in vitro antiproliferative effects of TCEO on A549, HepG2, MCF-7 cancer cells, and HUVEC non-tumor cells was investigated using an MTT assay. Flow cytometry analysis was conducted to evaluate cell cycle distribution using propidium iodide staining, and cell death mode using Annexin V-FITC/PI assays. The expression of some apoptosis related genes was investigated using qRT-PCR. Major constituents of TCEO included fenchol, borneol, 3-cyclohexene-1-methanol and 3-ethyl-3-methyl. Cell viability test showed that TCEO is highly effective against MCF-7 cells with IC50 12.5 µg/mL. Cell cycle arrest at the G1/S phase, and apoptosis mediation were evident in the presence of TCEO. Gene expression analysis of several pro-apoptotic and anti-apoptotic genes revealed the initiation of apoptosis in TCEO-MCF-7 cells. In conclusion, our study confirms the antiproliferative activity of the T. camphoratus essential oil.